Improvement of Magnetic Properties and Texture of FePt Thin Films on MgO Substrates by Sn Addition - Chun, DongWon; Kim, SungMan; Kim, GyeungHo; Jeung, WonYoung (KOREAN MAGNETICS SOC, 2009)
In this work, we studied the effects of Sn addition on the ordering temperature of FePt thin film. The coercivity of FePtSn film was about 1000 Oe greater than the coercivity of FePt film for an annealing temperature of 600 degrees C. Therefore, Sn addition was effective in promoting the L1(0) ordering and in reducing the ordering temperature of the FePt film. From our X-ray diffraction results, we found that in the as-deposited film, the addition of Sn induced a lattice expansion in disordered FePt thin films. After the annealing process, the excess Sn diffuses out from the ordered FePt thin film because of the difference in the solid solubility of Sn between the disordered and ordered phases. The existence of precipitates of Sn from the FePt lattice was deduced by Curie temperature measurements of the FePt and FePtSn films. Therefore, the key role played by the addition of Sn to the FePt film can be explained by a reduction in the activation energy for the L1(0) order-disorder transformation of FePt which originates from the high internal stress in the disordered phase induced by the supersaturated Sn atoms.
Keywords: MICROSTRUCTURE; TEMPERATURE; ALLOY; AG